Reducing Repeat Emergency Department Visits for Low-Acuity Patients Using a Healthcare Connection Program - Mitchell Hoyer; Kimberly A. Stanford; Ernestina Perez; Rachel Nordgren; Laura Markin; Melanie Francia; Zain Abid; Marika Kachman; Brenda Battle; Thomas Spiegel (Western Journal of Emergency Medicine)
Background: Emergency department (ED) utilization for non-emergent issues has been a longstanding issue in the United States, especially in service areas with high Medicaid enrollment. The Medical Home and Specialty Care Connection Program (MHSCC) at University of Chicago Medicine (UCM) supports patients recently seen in the ED with follow-up care by assisting patients with follow-up appointments, establishing a medical “home” and providing education on primary care utilization via working with a patient advocate. These types of programs have inconsistent results throughout the literature and a dearth of study periods. We conducted a program evaluation to assess the association of the MHSCC in reducing low-acuity ED utilization for program patients. Methods: This program evaluation used retrospective data from the MHSCC program dataset from 2012–2020 and matched with electronic health records of low-acuity ED visits at UCM ED from 2010–2022 for each patient. Pre- and post-low-acuity ED visit rates were calculated based on the patients first program enrollment and compared using the Wilcoxon signed-rank test. Results: In total 5,482 ED patients enrolled in the program were included in the sample, 537 of whom were enrolled more than once. These patients had 41,530 low-acuity ED visits. The rate of low-acuity ED visits after the program enrollment was significantly lower than before with a mean of 2.5 visits per year before program intervention to 1.38 after, a 45% decrease ( P<.0001). This resulted in an estimated 9,487 fewer low acuity ED visits over nine years. Patients with multiple enrollments (up to four) further resulted in a slightly lower ED visit rates. Patients who benefitted the most in both proportion and mean analyses were of low acuity. Conclusion: We found a significant reduction in program patient’s ED visit rates for low-acuity needs. Further evaluation on the outcomes of the program, mechanisms of physician referrals and attributes of the patient population are recommended to understand what drives these findings.